Role of L-cysteine and CdS as promoted agents in photocatalytic activity of TiO2 nanoparticles. Issue 6 (December 2019) - Karimzadeh, Sajad; Bahrami, Kiumars
Abstract: The present investigation has developed new TiO2 -based nanocomposites to increase its photo-catalytic activity. L-cysteine doped TiO2 /CdS with different weight percentages of L-cysteine (0.5, 1, 1.5, 2 and 2.5 wt.%) and CdS nanoparticles (5, 10 and 15 wt.%) were synthesized and their chemical properties were evaluated using XRD, FTIR, DRS, FESEM and PL analyses. The DRS results show that pure TiO2 and L-cysteine-TiO2 /CdS are UV-active and visible-active, respectively. Also, the PL analysis confirms low recombination rate of charge carriers for L-cysteine doped TiO2 /CdS nanocomposites. Photo-catalyst activity of the prepared nanocomposites (pure TiO2, L-cysteine doped TiO2 and L-cysteine doped TiO2 /CdS) was evaluated during degradation of methyl orang (MO), methylene blue (MB) and rhodamine B (RB) as azo dyes. As a result, L-cysteine (2%) doped TiO2 /CdS (10%) was completely removed 10 mg of MO, MB and RB under visible light irradiation after 210, 200 and 180 min, respectively. Also, the kinetic study indicates that the rate constant of L-cysteine (2%) doped TiO2 /CdS (10%) for RB, MO and MB photodegradation is 0.0261, 0.0124 and 0.0137 min −1, respectively.